Design of Columns Subject to Biaxial Bending - Springfield, John (Engineering Journal, 1975)
Task Group 3 of the Column Research Council is charged with seeking improved methods for the design of columns subject to biaxial bending. As a result of recent research, this Task Group now can recommend improved design techniques for the most commonly used type of steel column, namely the wide flange shape. It is the purpose of this paper to review the existing AISC Specification design requirements for biaxially loaded beam-columns, to present the proposed new design procedures, and to compare the size of column section required by the existing and proposed design rules for several practical design problems.